ANALISIS TINGKAT KECANDUAN GAME PADA SISWA SERTA IMPLIKASI DALAM BIMBINGAN DAN KONSELING - NURUL JANNAH; WIDYA KARTIKA SARI (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2019)
This study aims to determine the level ofaddiction game in students. This study uses a quantitative approach with a descriptive type. The population of the study was all students of SMP N 25 in Padang City, amounting to 739 people, a sample of 266 people selected using the stratified random sampling technique. The instrument used was a questionnaire with a reliability of 0.870 (addiction game). Data were analyzed by descriptive statistical techniques. The results of the study show (1)addiction game to students is generally in the high category, (2) the implementation of guidance and counseling can be designed guidance and counseling service programs to reduce the level of game addiction to students.